Rekonstruksi dan Reposisi Nurcholish Madjid Sebagai Ekonom Islam Indonesia - Ahmad Ubaidillah; Misbahul Khoir (JES (Jurnal Ekonomi Syariah), 2023)
The books of contemporary Islamic economic thought history circulating in Indonesia are dominated by Islamic economic thinkers or Islamic economists who come from abroad. Indonesian Islamic economists are hardly included in the literature. Indeed, there are quiet a few Islamic economic figures from Indonesia who are included. Researchers usually study Islamic economic thinking from a figure who is already commonly known as an Islamic economist. This means that the figure has researched and written a number of works specifically discussing Islamic economics. This paper aims at elaborating Nurcholish Madjid’s Islamic economic thought. This study applies qualitative that produces descriptive data in the form of written or spoken words from people and observable behavior which aims to explain and test the truth of an economic knowledge based on Islamic values. Sources of data used in this study are primary data sources and secondary data sources. The analytical method used in this research is hermeneutics. The results of the study show that there are several ideas of Nurcholish Madjid’s Islamic economics: economic justice, religious socialism, riba economics, business ethos, and business spirituality.